2018
DOI: 10.1111/fwb.13191
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale environmental flow results in mixed outcomes with short‐term benefits for a semi‐arid floodplain plant community

Abstract: Demonstrating and predicting the effectiveness of environmental watering to maintain ecosystem health is becoming increasingly important, notably in semi‐arid floodplain ecosystems. Modelling plant floodplain vegetation responses to inform environmental watering outcomes is also challenging. We evaluated the effects of a large‐scale environmental flow event on a semi‐arid floodplain lakeside plant assemblage for meeting the management goal of increasing water‐dependant taxa and functional groups. We developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Environmental flows reinstate important aspects of the natural flow regime and support native fish populations by providing longitudinal connectivity of riverine habitats, flow-based cues for spawning and migration, riverfloodplain connection and suitable physical and hydraulic habitats (Arthington, 2012;King, Ward, O'Connor, & Green, 2010;. As the specific flow needs of different biota are quite variable (e.g., Beesley et al, 2014;Moxham, Kenny, Beesley, & Gwinn, 2018;Poff & Zimmerman, 2010), the development of appropriate flow regimes requires a robust understanding of flow-ecology relationships (Arthington, Naiman, Mcclain, & Nilsson, 2010;. In most instances, quantitative relationships are lacking and management is based on generic, often unvalidated, flow-ecology relationships derived from limited data sets or expert opinion (Davies et al, 2014;Gwinn, Beesley, Close, Gawne, & Davies, 2016).…”
mentioning
confidence: 99%
“…Environmental flows reinstate important aspects of the natural flow regime and support native fish populations by providing longitudinal connectivity of riverine habitats, flow-based cues for spawning and migration, riverfloodplain connection and suitable physical and hydraulic habitats (Arthington, 2012;King, Ward, O'Connor, & Green, 2010;. As the specific flow needs of different biota are quite variable (e.g., Beesley et al, 2014;Moxham, Kenny, Beesley, & Gwinn, 2018;Poff & Zimmerman, 2010), the development of appropriate flow regimes requires a robust understanding of flow-ecology relationships (Arthington, Naiman, Mcclain, & Nilsson, 2010;. In most instances, quantitative relationships are lacking and management is based on generic, often unvalidated, flow-ecology relationships derived from limited data sets or expert opinion (Davies et al, 2014;Gwinn, Beesley, Close, Gawne, & Davies, 2016).…”
mentioning
confidence: 99%
“…The main claim for 'basin scale changes' is increased vegetation diversity, but the original data show high response variation at only a few sites (Capon and Campbell 2017) and there is no evidence provided by the authors to demonstrate these responses are more than short term. In fact, Moxham et al (2019) found only temporary, localised responses of floodplain plant communities to environmental watering. Gawne et al (2020) also reported mostly short term, localised responses, stating: 'the monitoring programme is showing promise with short-term responses being observed and longterm patterns being recorded', but presented no evidence of long-term patterns.…”
Section: The Murray-darling Basin Plan Is Delivering On Ecological Outcomesmentioning
confidence: 94%
“…For example, increased vegetation diversity was recorded at only a few sites and these showed highly variable responses (Capon and Campbell 2017). Moxham et al (2019) found only temporary, local responses by floodplain plant communities to environmental watering. Gawne et al (2020) reported short-term, localised responses, stating that 'the monitoring program is showing promise with short-term responses being observed and long-term patterns being recorded', but presented no evidence for the latter claim.…”
Section: Introductionmentioning
confidence: 92%